Pontuação e sintaxe em impressos portugueses renascentistas - Rosa, Maria Carlota Amaral Paixão (1994)
Before the appearance of the first grammars on the Portuguese language and the first orthographic treatises, the punctuation in the texts printed in Portuguese had as a model the Latin punctuation. However, transferring the punctuation from a language into a language has led to a reduction and consequent reinterpretation of the function of the signals. If, for the Latin grammarians, the punctuation indicated whether the meaning was complete or not, for the printer, who was responsible for the spelling of texts in Portuguese, the punctuation began to mark boundaries of prayer. At the same time, the standardization of Portuguese began, and with this, the inventory of punctuation marks in vernacular texts began to grow. And, together with the capital letter, the punctuation began to fix the notion of sentence spelling. In short, the analysis, based on the theory of variation, provides evidence that: a) there were punctuation contexts and no punctuation contexts; b) coma and colon were used in the same contexts, but began to specialize their functions; c) coma was being introduced into vernacular texts; d) the spelling sentence was coming up.